Applications of a high-throughput screen detecting CRISPR-Cas spacer acquisition - Cannon, Christopher (2025)
The arms race between prokaryotes and their foreign genetic elements has driven the evolution of a diverse and enigmatic array of immune systems. CRISPR-Cas systems uniquely provide adaptive immunity against these foreign elements. Immunity is achieved through the acquisition of DNA fragments derived from invaders’ genomes, catalysed by the Cas1-Cas2 integrase complex. These fragments are stored as spacers within CRISPR arrays and are transcribed to specifically direct the effector machinery against their complementary sequences.